Effects of water saturation on P-wave anisotropy in the Mancos Shale at seismic frequencies - Mikhaltsevitch, Vassili; Lebedev, M.; Gurevich, B. (2017)
We studied the influence of distilled water saturation on the P-wave anisotropy of the Mancos Shale in the range of the seismic frequencies from 0.1 Hz to 100 Hz. The measurements were conducted on two specimens cored in vertical and horizontal directions with respect to the formation bedding. The specimens were saturated with water at six relative humidities varying from 9% to 97.5%. The measurements show an increase in the components of the elastic stiffness tensor determining P-wave anisotropy with increasing saturation, which is especially noticeable for the saturations corresponding to relative humidities of 71% and 97.5%. Our experiments demonstrate a significant dispersion of the P-wave anisotropy when the shale is saturated at relative humidities of 71% and 97.5%.